Conditional Cash Transfers in Brazil: Treatment Evaluation of the 'Bolsa Família' Program on Education - Elke Schaffland (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
Brazil's 'Bolsa Família' conditional cash transfer program (BFP) is the most substantial poverty alleviation program in Brazil. It is the biggest program of this kind in the world, reaching more then 13 000 000 families. The BFP awards grants to eligible poor families, allowing increased consumption in the short term, while building human capital in the long term through setting requirements for school attendance and health care. In this paper, we evaluate the effect of these transfers on educational outcomes in 2004 and 2006, as well as heterogeneous treatment effects over age, region, gender and area (rural/urban). Using Propensity Score Matching (PSM), we find that the probability of school enrollment rises by around 4 percentage points for recipients' children. The effect is higher for younger children, as well as children living in less developed regions (north and north east) and rural areas. Our results also point to a positive impact on school attendance; recipients miss less school than non-recipient children. However, we also find that this result slightly fades over time.
Keywords: 330; conditional cash transfers; propensity score matching; education